Kontakty prof. Ignacego Chrzanowskiego z Poznaniem = Prof. Ignacy Chrzanowski's Contacts with Poznań - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper treats of Prof. Ignacy Chrzanowski's contacts with Poznań, who was an outstanding scholar of the history of Polish literature. As a Professr from the Jagellonian Univetsity of Cracow he conceived a whole-hearted affection for the Capital of Great-Poland (Wielkopolski) and influenced the shape of their inhabitants'humanistic culture by lectures, articles and the education of four students by name of S. Pigoń, R. Pollak, K. Chodynicki and S. Tync, who later became professors of the Poznań University. For his excellent achievements and co-operation with this young Academy the Poznań University in 1938 confered on Prof. Ignacy Chrzanowski the title of a doctor honoris causa.
Keywords: Chrzanowski, Ignacy (186-1940)